Word processing systems. ([New York, Geyer-McAllister Publications], 1979)
"The magazine of automated information services."
ABI/INFORM
Computer & control abstracts
Electrical & electronics abstracts
Physics abstracts. Science abstracts. Series A
Keywords: Word processing -- Periodicals